(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Right to Educationis the primary right of every citizen of India, whether a child resides in ahigh profile society or in a faraway not so developed secluded village,according to the Article 45 of Indian Constitution the basic elementaryeducation must be provided to all the children up to the age of fourteen years.Even after 64 years of independence some States in India are still strugglingto achieve Universal enrolment, retention and quality education. There areabout 1303996 or more than one million rural schools among 6,38,000 villages inIndia. Schools in rural areas are promoted to raise the level of education andliteracy in rural India. The main aim of running these types of schoolsin India is to increase the rate ofliteracy in rural areas. More than 40 percent of India’s population isilliterate and cannot read or write. Schools in rural areas are inadequate andoften equivalent to being non-existent. Thus, government’s initiative to set upschools in rural areas came into picture. According to Just Indian Schools theconditions of rural education in India, is improving steadily and the governmentis also providing full support and providing with many initiatives. The feestructure in these schools is also very low so that every child can study andafford it.